A CFD methodology for mass transfer of soluble species in incompressible two-phase flows: modelling and applications - Gennari, Gabriele (2023)
Continuous flow chemistry is an interesting technology that allows to overcome many of the limitations in terms of scalability of classical batch reactor designs. This approach is particularly relevant for both photochemistry and electrochemistry as new optimal solutions can be designed to limit, for example, the issues related to light penetration, reactor fouling, excessive distance between electrodes and management of hazardous compounds, whilst keeping the productivity high. Such devices operate often in a two-phase regime, where the appearance of a gas in the form of a disperse bubbly flow can be either a desirable feature (e.g. when the gas is needed for the reaction) or the result of a spontaneous reaction (e.g. electrochemistry). Such systems are very complicated flows where many bubbles populate the reactor at the same time and deform under the effect of several forces, such as surface tension, buoyancy and pressure and viscosity terms. Due to the solubility of gas in the liquid solvent, the disperse phase exchanges mass with the liquid (where the reactions generally occur) and the volume of the bubbles changes accordingly. Such physics is mainly a convection-dominated process that occurs at very small length scales (within the concentration boundary layer, which is generally thinner than the hydrodynamic one) and numerical tools for routine design are based on simplifying assumptions (reduced order methods) for the modelling of this region. However, such approaches often lead to errors in the prediction of the mass transfer rate and a fully-resolved method is generally needed to capture the physics at the interface. This last approach comes with a high computational cost (which makes it non suitable for common design processes) but can be employed in simplified scenarios to explore fundamental physics and derive correlation formulae to be used in reduced order models.